Félix Alberto Companioni Landín, PhD, example of researcher and professor in Cuban Dentistry - Sol Ángel Rosales Reyes (Universidad de Ciencias Médicas de La Habana, 2018)
Félix Alberto Companioni Landín, PhD, is a Doctor of Philosophy and an unquestionable example for all teachers and professionals of Cuban Dentistry. The main objective of this life history is to spread information about his professional career as a professor, teacher, and researcher. The most important sources of information used to write this article were his curriculum vitae and an interview made to him. After graduating as a nurse, he began the studies of Dentistry, and he later became a professor of Human Anatomy and an enthusiastic researcher. He graduated as Doctor in Specific Sciences in 1975, and Doctor of Philosophy with the presentation of his book and research named Contribución a la Historia de la Estomatología Cubana. He is also author of several textbooks and scientific articles, which were written especially for the studies of Dentistry. He received the Scientific Merit Award for all his life´s work in the 42nd edition of the Annual Health Prize of Public Health.   Companioni Landín is a personality in the field of Cuban Dentistry, and an example of professor and researcher, with a notorious scientific activity not only in his specialty (Human Anatomy), but also in the History of Dentistry. He earned the merit of being the first dentist who, during the revolutionary period, hold a place as Honorary Academician of the Academy of Sciences of Cuba. Keywords: Félix Companioni Landín, history of Cuban Dentistry, Human Anatomy, Honorary Academician, Cuban Dentistry, Scientific Merit Award.